Improvement of survival rates in the last decade in Thai childhood-onset systemic lupus erythematosus - Pondtip Jongvilaikasem; Edward B. McNeil; Pornsak Dissaneewate; Prayong Vachvanichsanong (BMC, 2018)
Abstract Background Morbidity and mortality in childhood onset systemic lupus erythematosus (SLE) is more severe than adult onset SLE. Long-term follow up is needed to determine the prognosis. The objectives of this study are to describe the mortality of childhood SLE in a single tertiary care centre over three decades, compare trends in survival over time, and determine predictors for survival. Methods We retrospectively reviewed the medical records of children aged < 18 years who were diagnosed with SLE at the Department of Pediatrics, Songklanagarind Hospital, Thailand, from 1985 to 2016. Results There were 331 children (272 girls, 59 boys) with a mean age at presentation of 11.5 ± 2.6 years. The mean follow-up duration was 7.0 ± 5.0 (range 1-28) years, 77 children (23.3%) died, 28.6% within the first year after diagnosis. The overall mortality rate was 3.3 per 100 person-years. Survival rates at 1, 5 and 10 years were 93.4%, 83.1% and 72.6%, respectively. Ten-year survival rates for the children diagnosed in the decades 1985-1996, 1997-2006 and 2007-2016 were 67.4%, 63.4% and 82.8%, respectively (p < 0.001). Boys had worse survival than girls (hazard ratio = 2.3, 95% CI: 1.4-3.7) even after adjusting for decade of diagnosis. Lupus nephritis (LN) class IV had similar survival compared to LN classes II/III/V combined (hazard ratio = 1.0, 95% CI: 0.6-1.7). Conclusion In our setting, the survival rate of childhood onset SLE has improved during the past 10 years, but mortality is still high compared to developed countries, particularly in boys.